PAI-1: An Integrator of Cell Signaling and Migration - Ralf-Peter Czekay; Cynthia E. Wilkins-Port; Stephen P. Higgins; Jennifer Freytag; Jessica M. Overstreet; R. Matthew Klein; Craig E. Higgins; Rohan Samarakoon; Paul J. Higgins (International Journal of Cell Biology)
Cellular migration, over simple surfaces or through complex stromal barriers, requires coordination between detachment/re-adhesion cycles, involving structural components of the extracellular matrix and their surface-binding elements (integrins), and the precise regulation of the pericellular proteolytic microenvironment. It is now apparent that several proteases and protease inhibitors, most notably urokinase plasminogen activator (uPA) and plasminogen activator inhibitor type-1 (PAI-1), also interact with several cell surface receptors transducing intracellular signals that significantly affect both motile and proliferative programs. These events appear distinct from the original function of uPA/PAI-1 as modulators of the plasmin-based proteolytic cascade. The multifaceted interactions of PAI-1 with specific matrix components (i.e., vitronectin), the low-density lipoprotein receptor-related protein-1 (LRP1), and the uPA/uPA receptor complex have dramatic consequences on the migratory phenotype and may underlie the pathophysiologic sequalae of PAI-1 deficiency and overexpression. This paper focuses on the increasingly intricate role of PAI-1 as a major mechanistic determinant of the cellular migratory phenotype.